Current state of prevalence and dynamics of alcohol-associated narcopathology: a retrospective study - S. N. Alekseenko; S. V. Gubarev; D. A. Lyubchenko; A. N. Redko (Кубанский научный медицинский вестник, 2022)
Background. The population prevalence of alcohol abuse-associated drug-related diseases bears high social impact. This indicator holds special value both as a potential indirect estimator of the quality of life, availability and efﬁciency of drug addiction treatment, a well as parameter for qualitative prognostic models of social and economic development. The burden of alcohol-associated drug diseases is typically ambiguous in prevalence estimation, both across Russian Federation and worldwide.Objectives. A study of the alcohol abuse-associated drug-related morbidity prevalence in Krasnodar Krai for period 2000–2020.Methods. A retrospective descriptive study included legal-paper data of the “Information on Drug-Related Disorders” federal statistics survey (Form 11) of Krasnodar Krai, years 2000-2020, describing the re-registration rate of alcohol use-associated drug disorders. The inclusion criterion was an established drug-related disease among all age cohorts. The main study indicators were regional prevalence values of alcoholic psychosis, alcohol dependence syndrome and harmful alcohol use relative to gender, area and age.Results. Prevalence trends in alcohol use-related drug pathology were more favourable in Krasnodar Krai over Southern Federal District and country-wide. The decline rate among males was signiﬁcantly higher (22.1-fold) vs. the female population (3.0-fold). The prevalence of alcohol use-related drug pathology remained higher in urban vs. rural areas, with higher rural vs. urban decline rates. Over the entire study period, the 40–59 years-age population was leading by the incidence of overall alcohol use-related drug pathology and, separately, of alcoholic psychosis and alcohol dependence syndrome. Highest harmful alcohol use values were registered for 20–39-year population.Conclusion. The revealed dynamics of legal-registered alcoholic drug pathology prevalence has a multifactorial origin. The changes are conditioned by improvement in the narcological aid institutional regulation within the state guarantee programme, federal and regional preventive measures, current progress in drug therapy, regional demography, as well as underreporting of alcohol-associated drug diseases due to a missing strict vertical statistic registration at the level of any-type medical institutions.